You are not a gadget : a manifesto - Lanier, Jaron (New York : Alfred A. Knopf, 2011)
Silicon Valley visionary Jaron Lanier was among the first to predict the revolutionary changes the World Wide Web would bring to commerce and culture. Now, in his first book, Lanier offers this cautionary look at the way the Web is transforming our lives, for better and for worse. The current design and function of the web have become so familiar that it is easy to forget that they grew out of programming decisions made decades ago. The web's first designers made crucial choices with enormous-and often unintended-consequences. What's more, these designs quickly became "locked in," a permanent part of the web's very structure. Lanier warns that our financial markets and sites like Wikipedia, Facebook, and Twitter are elevating the "wisdom" of mobs and computer algorithms over the intelligence and judgment of individuals. This book is a deeply felt defense of the individual, from an author uniquely qualified to comment on the way technology interacts with our culture.--From publisher description.
What is a person? -- Missing persons -- An apocalypse of self-abdication -- The noosphere is just another name for everyone's inner troll -- What will money be? -- Digital peasant chic -- The city is built to music -- The lords of the clouds renounce free will in order to become infinitely lucky -- The prospects for humanistic cloud economics -- Three possible future directions -- The unbearable thinness of flatness -- Retropolis -- Digital creativity eludes flat places -- All hail the membrane -- Making the best of bits -- I am a contrarian loop -- One story of how semantics might have evolved -- Future humors -- Home at last (my love affair with Bachelardian neoteny).
Keywords: Information technology -- Social aspects; Technological innovations -- Social aspects; Technology -- Social aspects